Money Supply and Inflation: Disaggregated Time Series Evidence from Nigeria - Ikezam, Nwonodi Daniel (American Finance & Banking Review, 2018)
This paper examined money supply and inflation in Nigeria. The objective was to examine the extent to which components of money supply affect Nigerian inflation rate. Time series data was sourced from Central Bank of Nigeria (CBN) statistical bulletin and Stock Exchange Factbook. Nigerian Real Inflation Rate was proxy for dependent (INFR) variables while Currency in Circulation (CR), Demand Deposit (DD), Time Deposit (TD), Savings Deposit (SD) and Net Foreign Asset (NFA) were used as independent variables. The Ordinary Least Square (OLS) method of cointegration, Augmented Dickey Fuller Unit Root, Granger Causality was used as data analysis techniques. Regression result in the study shows that Currency in Circulation, Demand Deposit and Savings Deposit has negative relationship while Net Foreign Asset and Time Deposit have positive relationship with inflation. The Augmented Dickey Fuller Test proved non stationarity of the variables at level except Net Foreign Asset but stationary at first difference. The Granger Causality Test reveals no casual relationship running through the variables. The cointegration proved no long run relationship between the dependent and independent variables. The study conclude that Money Supply have significant relationship with Nigerian Inflation Rate. It therefore recommends effective management of money supply by the monetary authorities to achieve the monetary policy objectives of price stability.